Tamerlane : Sword of Islam, Conqueror of the World - Marozzi, Justin (London Harper Perennial, 2005)
A powerful account of the life of Tamerlane the Great (1336-1405), the last master nomadic power, one of history's most extreme tyrants, and the subject of Marlowe's famous play. Marozzi travelled in the footsteps of the great Mogul Emperor of Samarkland to write this wonderful combination of history and travelogue.
Include Maps, Illustrations, Bibliography and Index
Keywords: Timur, 1336-1405 -- Conquerors -- Mongols--Kings and rulers